Технология швейных изделий: учеб. пособие / Левицкая Л. В. - Левицкая Любовь Васильевна (МОПИ, 1989)
Экземпляры: ТО (20100629) / Инвентарный номер: 943843 / Цена: 0.70 / Сис.шифр: 37.24 / Авт.знак: Л 37 / ГРНТИ: 64 / ББК: 37.24